The Shadowed Identity as a Social-Cultural Quality of “The Man of the Crowd” - Babajanyan, Levon (Bulletin of Yerevan University E: Philosophy, Psychology, 2015)
In the article, the history of the civilisation is observed as a history of man and society rationalisation. One of the breaking (crucial) points in the rationalisation of the civilization was the modernisation enlightening project. However, as a result of some civilizational, anthropological, and political transitions, enlightening project of modernisation is split between cultural and civilisation modernisation projects, because of which occurs a disproportion between society’s cultural and civilisation rationalities. This finally leads to the formation of mass society, where the 34 main character of socio-cultural relations becomes the so-called “the man of the crowd”. Appearing on the stage of civilisation based on rationality the man of the crowd, however, illustrates the irrational socio-cultural behaviour. The point is that the man of the crowd has shadow qualities suppressed because of transition from pre-civilization to civilization state, alienated, closed in the prison of unconsciousness. As an implication of realisation of the modernisation project, the shadowed identity of a man which is alienated by rationality becomes a socio-cultural quality of the man of the crowd.